Енергетичний метод розрахунку параметрів процесу пластичної деформації поверхні при віброобробці - Журавлева, Людмила Александровна; Яковенко, Валерий Владимирович; Калмыков, Михаил Александрович; Струтинский, Василий Борисович (Eastern-European Journal of Enterprise Technologies, 2010)
The issues of energy essence of the phenomena that occur in the surface layer under deformation, and so we consider the theory of deformation and structural and energetic analysis of vibrotreatment metal surface